Decadal change of rainfall erosivity during rainy season in mainland China and its underlying causes - Cao, Qing; Yuan, Xing; Yan, Qingyun; Zhu, Feilin (Journal of hydrology (Amsterdam), 2023)
[Display omitted] •Rainy-season rainfall erosivity in China has decadal change around 2003 and 2008.•Pacific Decadal Oscillation modulated rainy-season rainfall erosivity in the Yangtze River basin and the source of three rivers.•Atlantic and Indian Ocean warming affected rainy-season rainfall erosivity in northeastern and north China.•The effect of sea surface temperature on rainy-season rainfall erosivity in sub-regions was shown as different resonant periods. Rainfall erosivity is a crucial indicator of soil erosion that affects sediment management and agricultural security. Understanding the decadal change of rainfall erosivity during rainy season (RERS), when soil erosion occurs most frequently, is critical for environmental management and agricultural planning under climate change. However, whether RERS in mainland China has experienced decadal change and how it responds to large-scale climate indicators is unclear. Here, the decadal changes of RERS over mainland China and its underlying causes according to climate factors are investigated. The multi-scale moving t-test was used to determine the rainy season, and the rotated empirical orthogonal function analysis was applied to divide mainland China into sub-regions. Three abruption-detection methods were used to determine the decadal variation of RERS. Results show that: (1) RERS in China experienced different decadal change characteristics in different sub-regions. In the Yangtze River basin and the source of three rivers, the decadal change of RERS occurred around 2003, while RERS showed a prominent increasing trend over northeastern and northern China after 2008. (2) Significant negative (positive) trend of RERS over the Yangtze River basin (the source of three rivers) after 2003 was related to enhanced monsoon and anomalous divergence (convergence) modulated by Pacific Decadal Oscillation (PDO). By contrast, the prominent increasing trend after 2008 over northeastern and northern China was correlated to the Northern China Cold Vortex and Atlantic and Indian Ocean warming. (3) The non-stationary characteristic between sea surface temperature (SST) and RERS was reflected by the cross-wavelet transform. The influence of PDO over the Yangtze River basin and the source of three rivers was shown as long-term (8–13 years) or short-term (2–6 years) resonant periods. In contrast, the effect of SST over the Indian Ocean and the Atlantic Ocean is mainly presented as short-term resonant periods. These results suggest that the decadal change of RERS is closely related to the changes in SST and particular atmospheric circulation, and understanding these oceanic and atmospheric dynamics is helpful for agricultural security and environmental management under RERS changes.